PERKEMBANGAN INDUSTRI LITIK PENGHUNI GUA-GUA DI JAWA TIMUR - Indah Asikin Nurani (Berkala Arkeologi, 2004)
The influence of raw material is seen on the size of the tool. In the cave group on Mount Watang that uses rocks with a low level of silica (limestone), reliable artisan is demanded. This is because rock types are brittle and flaking them is difficult. Stone tool products in this group show a relatively large size due to the suboptimal flaking. Meanwhile, the stone tool products in the cave group in Sampung, Ponorogo is a microlithic. This is because the raw material has a relatively high level of silica (chert and chalcedony). The flaking techniques can be carried out optimally, resulting in small-sized stone tool products with micro trimming and flaking, both primary and secondary.